2008
DOI: 10.1002/aic.11424
|View full text |Cite
|
Sign up to set email alerts
|

Linear QSPRs for predicting pure compound properties in homologous series

Abstract: Linear QSPRs, containing 1 through 4 descriptors, are developed for predicting the normal boiling temperature, melting point temperature, and critical properties for the n‐alkane, 1‐alkene, n‐alkylbenzene, 1‐alcohol, and alkanoic monocarboxylic acid homologous series. It has been shown that property values for which experimental data are available can be predicted within experimental error level (with very few and very small exceptions), irrespective of whether interpolation or extrapolation is involved. Prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Brauner et al 12 suggested the use of linear QSPR models for predicting T m of members of homologous series. This method was demonstrated by developing a linear QSPR containing four molecular descriptors (five parameters) for the 1-alkanol homologous series.…”
Section: C 2013 American Institute Of Chemical Engineersmentioning
confidence: 99%
“…Brauner et al 12 suggested the use of linear QSPR models for predicting T m of members of homologous series. This method was demonstrated by developing a linear QSPR containing four molecular descriptors (five parameters) for the 1-alkanol homologous series.…”
Section: C 2013 American Institute Of Chemical Engineersmentioning
confidence: 99%
“…The T C data in Figure 6 exhibits some curvature which cannot be explained by a linear equation based on one descriptor. Indeed Brauner et al10 have shown that often more than one descriptor (typically two for T C ) are needed to represent the behavior of a property with high precision and random residual, for the range of n C values used here. We assume, however, that the additional curvature is caused by the influence of the specific functional group (COOH in this particular case) and its effect diminishes for long‐chain molecules.…”
Section: Use Of the Ivde Descriptor For Prediction Of Tc For Several mentioning
confidence: 99%
“…Current methods used to predict physical and thermodynamic properties can be classified into group contribution methods (GC2), asymptotic behavior correlations (ABCs3–6) and various quantitative structure property relationships (QSPRs7–10). All of these methods use available experimental data for low carbon number ( n C ) compounds to obtain either “group contribution” values or regression model parameter values.…”
Section: Introductionmentioning
confidence: 99%
“…The method began with the pioneering study of pesticides by Hansch et al In 1962, Mills et al first used QSPR to predict the melting and boiling points of organic compounds. Linear QSPRs were developed for predicting normal boiling temperature, melting temperature, and critical properties for several homologous series . With the development of QSARs/QSPRs, many studies have provided guidance on establishing correlation models …”
Section: Introductionmentioning
confidence: 99%